The 100 most significant events in American business : an encyclopedia - Skrabec, Quentin R. (Santa Barbara, Calif. : Greenwood, 2012)
Throughout history, important commercial developments in the United States have made it possible for American companies to leverage tough economic conditions to survive--even thrive in a volatile marketplace. This reference book examines the top 100 groundbreaking events in the history of American business and illustrates their influence on the labor laws, business practices, and management methodologies of corporate America today. The 100 Most Significant Events in American Business: An Encyclopedia depicts the chronological order of events contributing to the evolution of American business, with an emphasis on the commercial innovations of each period. The book explores the origins of successful brands, including Apple, Wal-Mart, and Heinz; demonstrates the successful collaboration between public and private sectors illustrated by the Erie Canal, Hoover Dam, and the interstate highway system; and depicts the commercial impact of major economic events from the Panic of 1857 to the Great Recession of 2009.
Privatization of the Plymouth Colony (1623) -- Navigation Acts (1651) -- Wealth of Nations (1776) -- Patent and copyright statutes (1790) -- "Report on manufacturing" (1791) -- Whiskey rebellion (1794) -- Jefferson embargo (1807) -- First steamboat to New Orleans (1811) -- National road (1811) -- Erie Canal (1825) -- Tariff of Abominations (1828) -- Baltimore & Ohio Railroad (1828) -- Whig Party evolves (1834) -- Panic of 1837 -- Automated sewing machine (1846) -- Revolution, famine, and immigration (1848) -- Clipper ships (1849) -- Western Union Telegraph Company (1851) -- Great Exhibition of 1851 -- Transatlantic Cable (1857) -- Panic of 1857 -- Overland travel and mail services (1859) -- Abraham Lincoln establishes protectionism (1860) -- World's largest cannon/Civil War technology (1864) -- Transcontinental Railroad completed (1869) -- Westinghouse air brake (1869) -- Panic of 1873 -- Andrew Carnegie's first steel mill (1875) -- Centennial exposition (1876) -- First commercial telephone (1877) -- Great Railroad Strike of 1877 -- World's first skyscraper (1884) -- War of the Currents (1885) -- Sears mail order business (1886) -- Haymarket Riot (1886) -- ALCOA aluminum formed (1888) -- McKinley Tariff of 1890 -- Homestead strike of 1892 -- Panic of 1893 -- Chicago World's Fair (1893) -- Pullman Strike (18940 -- Niagara Falls power plant (1896) -- Paternal capitalism-Homestead and Wilmerding, Pennsylvania (1896) -- First electric sign (product branding and advertising)-H. J. Heinz (1900) -- First billion-dollar corporation-United States Steel (1901) -- Henry Ford wins race of the century (1901) -- Owens automated glass bottle-making machine (1904) -- Upton Sinclair's Jungle (1905) -- Panic of 1907 -- Highland Park Ford assembly line (1910) -- Scientific Management (1911) -- Standard Oil antitrust lawsuit (19110 -- Income tax (1913) -- Federal Reserve Act 91913) -- Commercial flight (1914) -- Panama Canal opens (1914) -- General Motors Corporation formed (1916) -- Great Steel Strike of 1919 -- First commercial radio (1921) -- Hawthorne studies begin (1924) -- Talking movies-The Jazz Singer 91927) -- Stock market crash/Great Depression (1929) -- Hoover Dam (1931) -- National Labor Relations Act (Wagner Act) (1935) -- Social Security Act (1935) -- Television at the 1939 world's fair -- Maslow's theory of needs (1946) -- General Agreement on Tariffs and Trade (GATT) (1947) -- First credit card (1950) -- UNIVAC I (1951) -- Shippingport Atomic Power Station (1956) -- Federal Aid Highway Act of 1956 -- First mass-produced transistor radio (1957) -- First Japanese auto sold in the United States (1958) -- Steel Strike of 1959 -- America targets the moon (1961) -- McDonald's launches golden arches (1962) -- Telstar Communications Satellites (1962) -- First Wal-Mart (and Kmart) open (1962) -- IBM 360 Computer (1964) -- Unsafe at Any Speed (1965) -- ARPAnet (earliest internet) formed (1969) -- Wage and price controls (1971) -- Arab oil embargo (1973) -- First customer scan of a bar code (1974) -- The year of the PC (1977) -- Three Mile Island nuclear failure (1979) -- IBM personal computer (1982) -- FCC approves advanced mobile phone system (IG) (1982) -- Deindustrialization of America-General Tire Akron closes (1982) -- CD-ROM (1985) -- Savings and loan crisis (1986) -- W. Edwards Deming publishes Out of the Crisis (1986) -- Amazon.com (1994) -- Bill Gates internet memo (1995) -- Google Incorporated (1998) -- First 3G networks and the smartphone (2003) -- RFID at Wal-Mart (2005) -- Banking crisis and Great Recession (2008) -- General Motors bankruptcy (2009)
Includes bibliographical references and index.
Keywords: United States -- Commerce -- History -- Encyclopedias; Industries -- United States -- History -- Encyclopedias; Business -- History -- Encyclopedias